Analisis Flypaper effect pada Pendapatan Asli Daerah dan Dana Perimbangan terhadap Belanja Daerah Kab/Kota di Provinsi Jambi Tahun 2017-2023 - Alya Astrie Yonanda; Candra Mustika; Parmadi Parmadi (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the influence of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Tax Revenue Sharing Fund (DBHP) on Regional Expenditure, as well as to analyze whether the flypaper effect phenomenon occurs in Regencies/Cities in Jambi Province during the 2017-2023 period. The data used in this study is panel data that combines time series data for 7 years and cross-section data from 11 Regencies/Cities in Jambi Province. The analysis method used is panel data regression with the selected model Fixed Effect Model (FEM). The results of the study show that simultaneously (F Test), the variables PAD, DAU, DAK, and DBHP have a significant effect on Regional Expenditure. Partially (t Test), PAD and DBHP do not have a positive and significant effect on Regional Expenditure, while DAU and DAK show a positive and significant effect on Regional Expenditure. This study also found a flypaper effect in regencies/cities in Jambi Province. This indicates that regional governments in Jambi Province tend to be more responsive in increasing regional spending using transfer funds from the central government rather than optimizing their own potential Regional Original Revenue (PAD).